Sejarah Pembaruan Hukum Keluarga Islam Di Indonesia - Nurhikmah Hairak H. Biga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
Indonesian family law is the translation of family law in Islam. One problem that is regulated is the issue of marriage law. This marriage law in its development experienced a long journey in formation. In the history of the renewal of Islamic marriage law in Indonesia, there are three periods, namely the period before the arrival of colonialists, colonialism and independence. The independence period was divided into three periods, namely the old order, the new order and the reform period. During the old order, Law Number 22 Year 1946 and Law Number 32 of 1954 were born. In the New Order, Law Number 1 Year 1974 and Presidential Instruction Number 1 of 1991 were born regarding the Compilation of Islamic Law. During the Reformation, the Government and the Gender Mainstreaming Team designed a revised draft on Compilation of Islamic Law.